Fatigue behavior of damaged concrete beams repaired with composite material - Khamis Hadjazi; A. Hamiani; Sereir Zouaoui; Amziane Sofiane (Journal of Building Materials and Structures)
By the present paper, an analytical model was developed to study the cracked FRP-strengthened reinforced concrete beams subjected to fatigue loading. In order to follow the distribution of interfacial shear stresses causing the debonding phenomenon, a new analytical model based on the cohesive zone (CZ) approach was developed. The present model has the possibility to describe the evolution of the shear stress in the three zones (elastic, microcrack and debonding) and the bearing capacity of the repaired structure. Interface damage scenarios were evaluated for a fatigue load estimated to 90% of the elastic load and another at 60% of the ultimate load Pu.  Results obtained are in good agreement with those given by the literature. The results showed that the shear strength developed by the repaired beam is sensitive to the variation of the mechanical properties (Concrete, FRP and Adhesive layer), the fatigue load ratio and the number of cycles. These parameters can be considered as indicators of damage affecting the health status of the structure repaired during fatigue. The debonding at the FRP-concrete interface noticeably reduced the strength and lifespan of the repaired structure.